Research Progress in Regulation of Sulforaphane Synthesis in Broccoli Sprouts - LI Cui, FANG Sheng, ZHAO Zhongliang, LIU Haijie (Shipin Kexue)
Sulforaphane (SFN) has a variety of biological activities such as anti-tumor, anti-inflammatory, antioxidant, and anti-obesity properties. Being rich in SFN, broccoli sprouts are promising for application in the development of health foods and medicine. This article first reviews the synthesis and degradation process of SFN in broccoli sprouts, with a focus on the effects of different treatments on the contents of SFN and its synthesis-related factors during the growth of broccoli sprouts. It then summarizes the underlying mechanisms. Finally, the existing problems are outlined and future research directions are discussed, hoping to provide a reference for future research to improve the functionality of plant-derived foods.